AFFIXATION AS A HIGHLY PRODUCTIVE TYPE OF WORD FORMATION TYPES OF AFFIXES (Modern education and development, 2025)
This article explores affixation as a highly productive method of word formation in language, emphasizing its significance in expanding vocabulary. It defines affixation as the process of adding affixes to base words or stems to create new lexemes, thereby modifying their meanings or grammatical categories. The article categorizes affixes into five main types: prefixes, suffixes, infixes, circumfixes, and compound affixes, providing examples for each. It highlights the productivity of affixation in the creation of new terms, particularly in response to technological advancements and globalization. The article concludes by underscoring the role of affixation in the evolution of language, demonstrating its adaptability and capacity to reflect changing human experiences.